Penerapan Model Pembelajaran Paikem Dengan Teknik Communicative Drilling Untuk Meningkatkan Aktivitas Dan Prestasi Belajar - Sri Wigati (Cetta: Jurnal Ilmu Pendidikan, 2020)
This classroom action research was done at SMPN 1 Abang at grade VIII A that were still low in learning achievement and also in learning activities in English lesson especially at speaking class. This study aimed at knowing wether the implementation of PAIKEM as learning model combined with Communicative drilling can improve students’s speaking skill in English.The research data were students learning activities data and students learning achievement in english lesson.The students activities data were taken by using observation technique, while students learning achievement data were taken by students achievement in term of Basic competence test. The colected data were then analized in descriptive and qualitative method. The result of the research data analisys showed the mean of students learning activities at pre- sycle step was 63.33% then increased to 75.23 at sycle I and 86.19 at sycle II. While the mean point of students learning achievement showed 69,85 with the 40% in mastery learning then increased into 74.54 with 68% mastery learning at sycle I and at the sycle II the mean increased into 76.02 with 85% mastery learning. The reserach can be summerized that the implementation of PAIKEM learning model combined with Communicative drilling could increase the students learning activities and students learning achievement.